Immunoproteomics and phage display in the context of leishmaniasis complexity - Ludolf, Fernanda; Ramos, Fernanda F.; Coelho, Eduardo A. F. (Frontiers in Immunology, 2023)
Leishmaniasis is defined as a complex of diseases caused by protozoan parasites of the genus Leishmania, which comprises 20 parasite species pathogenic to mammalians, such as humans and dogs. From a clinical point of view, and considering the diversity and biological complexity of the parasites, vectors, and vertebrate hosts, leishmaniasis is classified according to the distinct clinical manifestations, such as tegumentary (involving the cutaneous, mucosal, and cutaneous-diffuse forms) and visceral leishmaniasis. Many issues and challenges remain unaddressed, which could be attributed to the complexity and diversity of the disease. The current demand for the identification of new Leishmania antigenic targets for the development of multicomponent-based vaccines, as well as for the production of specific diagnostic tests, is evident. In recent years, biotechnological tools have allowed the identification of several Leishmania biomarkers that might potentially be used for diagnosis and have an application in vaccine development. In this Mini Review, we discuss the different aspects of this complex disease that have been addressed by technologies such as immunoproteomics and phage display. It is extremely important to be aware of the potential applications of antigens selected in different screening context, so that they can be used appropriately, so understanding their performance, characteristics, and self-limitations.